AN ANALYSIS OF STUDENTS’ RESPONDING ASSESSMENT IN ANALYTICAL EXPOSITION TEXT - Christiana Meliana; Rafika Dewi Nasution; Anggarini Thesisia Saragih (Universitas Negeri Medan, 2020)
This study aims to analysis students responding assessment in analytical exposition text. The purpose of this research is to find out how students respond to understanding analytical exposition text. The subject of the research was the eleventh grade students of SMK SWASTA PAB 12 Percut sei tuan. The research design of this study was qualitatve research.The instruments for collecting data were assessment or questionnaire, observation, and interview. The data were gathered by administering interview to the teacher English and distributing questionnaire to the eleventh grade students. This study were the assessment of students’ responding at in the Eleventh grade students of SMK SWASTA PAB.Students responding occurs when a students make a response by answering questions or responding in a variety of ways that communicates the students’ understanding of the content being taught during the lesson. The researcher can concluded that there was 17 students who know and want respond to the feedback that the teacher gives to students in analytical exposition text material. Conversely there was 8 students who was unable to respond to the material because the ability to received and absorb analytical exposition material is not easy for them, so teachers must patiently guide and applied analytical exposition learning material to students who was poor response and absorbing abilities.65% of students can quickly respond to analytical exposition material used informal assessment methods and 35% of students can answer questions given by the teacher to students.Key Words: Qualitative Research, Writing, Assessment, Students’ Responding, Analytical Exposition Text.